Determinan Support System Dan Quality Of Life Pasien Pasca Covid-19 Di Kabupaten Ende, Provinsi Nusa Tenggara Timur - Irfan, Irfan; Artama, Syaputra; Wawomeo, Aris (JURNAL INFO KESEHATAN, 2022)
The impact of the COVID-19 pandemic has caused a change in habits for post-COVID-19 patients in Indonesia. Support system, both informal and formal, are very important for the successful treatment and recovery of post-COVID-19 patients. The level of knowledge, attitudes and behavior of the patient's family is also significantly influential on the support system, especially for comorbid patients who undergo a longer recovery process. The objective of this study to determine the determinants of the support system and quality of life in post-COVID-19 patients in Ende Regency. The type of research used is analytic observational using a cross sectional study design. The sampling method used cluster random sampling. The sample used proportional allocation technique with a sample of 110 respondents. The results of the study found that the variables that had a significant relationship with the support system and quality of life of post-COVID-19 patients were the respondent's age (p=0.001), quality of life (p=0.001), family attitudes (p=0.001), family behavior (p=0.001), health status (p=0.001) and the patient's comorbid history (p=0.001), while for family knowledge variables (p=0.051) and (p=0.129), and there is no significant relationship for symptoms when suffering from COVID-19 (p=0.078) and (p=0.717). The conclusion is that the support system provided to people with various determinants when facing the situation after the coronavirus pandemic is very important in improving the physical and psychological dimensions. A good support system can reduce various forms of stress, improve coping mechanisms and improve the quality of life of post-COVID-19 patients.